Embracing material surface imperfections in product design - Owain F. Pedgley; Bahar Sener; Debra Lilley; Ben Bridgens (2018)
Imperfection is not a usual aim within the context of industrialized product design. Under general norms, products are manufactured as clones of a ‘perfect’ original and product surfaces are prized for their ‘perfect’ flawless state. The mass production of products against these principles seems counterintuitive. Yet within the world of materials, and especially considering material surfaces, imperfection is widespread. This research set out to identify and scrutinize circumstances when material imperfection in products is appreciated, from mass manufacture to artisan practices. By synthesizing literature with analyses of material and product samples, five sources of surface imperfections are characterized: inherent material properties, production effects, workmanship of risk, planned and foreseen events, and everyday wear and tear. Following this, a research-focused concept design project is reported, leading to eleven product designs that exemplify how to design for, and with, imperfect material surfaces. A significant challenge facing designers is one of persuasion: of designing products where imperfect material surfaces are regarded as contributing to rather than detracting from product value. To this end, the paper culminates in a visual guide to embracing material surface imperfections in design practice.